2020
DOI: 10.23937/2572-3243.1510089
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Pain and Postural Abnormalities among Smartphone-Using Digital Natives

Abstract: The younger generations are labeled "digital native" among whom smartphone penetration and adoption is high. However, the health consequences of intense utilization of smartphones as a contributor to the increasing prevalence of musculoskeletal disorders in young adults are less explored. This study investigated patterns of musculoskeletal pain, postural abnormalities, and smartphone usage among undergraduate university students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Odole et al 2020 linked MSD pain to postural abnormalities and smartphone usage [15]. The authors evaluated 12 postures classified as good or faulty (based on the plumb line method proposed by [20]) on Nigerian students.…”
Section: In 2018 Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Odole et al 2020 linked MSD pain to postural abnormalities and smartphone usage [15]. The authors evaluated 12 postures classified as good or faulty (based on the plumb line method proposed by [20]) on Nigerian students.…”
Section: In 2018 Andmentioning
confidence: 99%
“…texting, web browsing, watching video, gaming, photos and selfies, and calling. They were obtained on the basis of works addressing the issue of postures when using smartphone [8,15,16,22,23,25,[27][28][29][30][31]. The synthesis of these works led to propose taxonomy of 41 postures called SmarTaxo (Table 1).…”
Section: Study Sample and Designmentioning
confidence: 99%
“…Musculoskeletal pain is extremely common regardless of age, gender, or socioeconomic status, making it common even in younger populations, especially pain in the neck, shoulder, and back. Studies have found a high prevalence of musculoskeletal pain in the student population, ranging from 51.7% to 54.5% (5). Pain is a very common feature of most MSDs.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have investigated smartphone activities to assess the prevalence of musculoskeletal disorders (MSDs) related to the upper limbs [ 11 ] upper extremities [ 12 ], or postures qualified as good or faulty [ 13 ]. Their research evaluated the duration and distribution of several smartphone activities among students, such as chatting, watching videos/movies, playing games, making phone calls, browsing the internet, blogging, making video calls, reading/studying, and engaging in photography.…”
Section: Introductionmentioning
confidence: 99%
“…Their research evaluated the duration and distribution of several smartphone activities among students, such as chatting, watching videos/movies, playing games, making phone calls, browsing the internet, blogging, making video calls, reading/studying, and engaging in photography. Balakrishnan et al [ 12 ] and Odole et al [ 13 ] provided data on user distribution within a 1–2 h time frame, including percentages for activities such as web browsing (21 % and 21.3 % for 5 h), phone calls (36 % and 28.5 % for 2 h), and watching videos and taking pictures (20 % and 41.3 % for 2 h), respectively. In contrast, Berolo et al [ 11 ] achieved greater precision when it came to mean durations.…”
Section: Introductionmentioning
confidence: 99%